2014
DOI: 10.1038/bjc.2014.61
|View full text |Cite
|
Sign up to set email alerts
|

HER2, MET and FGFR2 oncogenic driver alterations define distinct molecular segments for targeted therapies in gastric carcinoma

Abstract: Background:Gastric cancer (GC) is a leading cause of cancer deaths worldwide. Since the approval of trastuzumab, targeted therapies are emerging as promising treatment options for the disease. This study aimed to explore the molecular segmentation of several known therapeutics targets, human epidermal growth factor receptor 2 (HER2), MET and fibroblast growth factor receptor 2 (FGFR2), within GC using clinically approved or investigational kits and scoring criteria. Knowledge of how these markers are segmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
76
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 39 publications
(57 reference statements)
9
76
2
1
Order By: Relevance
“…Furthermore, 26% (24 of 93) of the amplifications were amplification of one of four genes (ERBB2, FGFR2, MET, and EGFR) that encode a RTK. The frequencies of these gene amplifications were not significantly different from those previously reported for ERBB2, FGFR2, 9,10,12,14 MET, 6,7,14,15 and EGFR. 6,20 It is intriguing that, except for case 7, RTK gene amplification occurred in a mutually exclusive manner.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Furthermore, 26% (24 of 93) of the amplifications were amplification of one of four genes (ERBB2, FGFR2, MET, and EGFR) that encode a RTK. The frequencies of these gene amplifications were not significantly different from those previously reported for ERBB2, FGFR2, 9,10,12,14 MET, 6,7,14,15 and EGFR. 6,20 It is intriguing that, except for case 7, RTK gene amplification occurred in a mutually exclusive manner.…”
Section: Discussioncontrasting
confidence: 76%
“…8,9 In preclinical studies, cells with amplified FGFR2 or MET showed overexpression of their respective proteins, and inhibitors to these receptors were shown to effectively block their downstream signal transduction and induce apoptosis. [10][11][12][13][14] At present, apart from ERBB2 targeting, approaches for targeting MET and FGFR2 are the most clinically advanced of prospective targeted therapy. However, the prevalence of amplification of each of these genes, as assessed by oligonucleotide array comparative genetic hybridization, real-time PCR, fluorescence in situ hybridization (FISH), or silver in situ hybridization is low, ie, from 2 to 5% for FGFR2, 9,10,12,14 and from 2 to 8% for MET, respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, recent IHC studies performed on gastric tumour samples have reported cMET over-expression in 4-63% of cases [72][73][74][75][76][77] and various studies performed in ovarian cancer estimate high expression of cMET to be present in 11-68 % of cases [30,22,23,26,25] (Table 1). The majority of the estimates above come from IHC studies, using a number of different antibodies, but no consensus on scoring criteria yet exists, nor whether cytoplasmic or membranous staining for cMET is important.…”
Section: Ihc For Cmetmentioning
confidence: 99%